Shengjiang San alleviated sepsis-induced lung injury through its bidirectional regulatory effect - Shifan Yan; Yu Jiang; Ting Yu; Changmiao Hou; Wen Xiao; Jing Xu; Huili Wen; Jingjing Wang; Shutong Li; Fang Chen; Shentang Li; Xiehong Liu; et al. (BMC, 2023)
Abstract Background Sepsis is a life-threatening organ dysfunction caused by dysregulated host responses to infection, for which effective therapeutic strategies are still absent. Shengjiang San (SJS), a well-known Traditional Chinese Medicine formula, has been widely used clinically. However, its role in sepsis-induced lung injury remains unclear. Methods To explore its specific mechanism, we firstly established a sepsis animal model using cecal ligation and puncture (CLP) and treated MH-S cells with LPS plus ATP. Then, UPLC/Q-TOF-MS/MS was utilized to identify its active ingredients. Network pharmacology analysis was performed to uncover the potential mechanism. HE staining and biochemical analysis were conducted to validate its therapeutic effect. ELISA was applied to detect the release of pro-inflammatory and anti-inflammatory cytokines. Western blot was utilized to detect the protein levels of GSDMD, NLRP3, P65, ASC and caspase-1. Results SJS could dramatically increase the survival rate of sepsis. In addition, it is able to inhibit the pro-inflammatory cytokines release at day 1 post CLP while promote their production at day 7, indicating SJS could attenuate uncontrolled inflammatory response in the early stage and improve immunosuppression in the late phase. Network pharmacology analysis showed that pyroptosis is the crucial action SJS exerted in the protection of sepsis-induced lung injury. Western blot data implicated SJS could attenuate pyroptosis in early sepsis while enhance in the late phase. Conclusions SJS acted to alleviate sepsis-induced lung injury through its bidirectional regulatory effect.